Hydrological impact assessment on permeable road pavement with subsurface precast micro-detention pond - Norazlina, Bateni; Lai, S.H.; Frederik Josep, Putuhena; Mah, D.Y.S.; Md Abdul, Mannan; Chin, Ren Jie (CWIEM, 2020)
The purpose of this paper is to study stormwater management potential of new permeable pavement with subsurface micro-detention storage (PPDS) at low-speed residential suburban area. The main features incorporated permeable pavement of a hollow micro cylinder precast structure with solid hexagon precast concrete as top and bottom covers. The purpose of hollow micro detention design is for rainwater holding and void between the sets is for self-drying through the side and bottom seepage during rain. The hydrological parameters were obtained from laboratory rainfall simulator experiment. The performance was evaluated via simulation with Storm Water Management Model (SWMM). The outcomes from the physical model matched well with SWMM. A case study was then developed to assess the hydrological impact of PPDS with the existing condition and other types of permeable pavements. Significant variance was observed, where PPDS displayed its best hydrological performances for stormwater management with the presence of subsurface detention storage.